2019
DOI: 10.1016/j.ijheh.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Selecting mixtures on the basis of dietary exposure and hazard data: application to pesticide exposure in the European population in relation to steatosis

Abstract: 33Populations are exposed to mixtures of pesticides through their diet on a daily basis. The 34 question of which substances should be assessed together remains a major challenge due to the 35 complexity of the mixtures. In addition, the associated risk is difficult to characterise. The 36EuroMix project (European Test and Risk Assessment Strategies for Mixtures) has developed 37 a strategy for mixture risk assessment. In particular, it has proposed a methodology that 38 combines exposures and hazard informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the authors in the context of a grant agreement between the European Food Safety Authority and the authors. In the EU-funded project EuroMix (Grant Agreement Number 633172) 10 useful tools have been surveyed, developed and/or implemented in the MCRA software, such as the Maximum Cumulative Ratio (MCR) method and the SNMU method, to diagnose mixtures of concern and the persons exposed to multiple pesticides (Crépet, 2019). It cannot be considered as an output adopted by the Authority.…”
Section: Co-exposure To Multiple Pesticides or Exposure To Single Pesmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the authors in the context of a grant agreement between the European Food Safety Authority and the authors. In the EU-funded project EuroMix (Grant Agreement Number 633172) 10 useful tools have been surveyed, developed and/or implemented in the MCRA software, such as the Maximum Cumulative Ratio (MCR) method and the SNMU method, to diagnose mixtures of concern and the persons exposed to multiple pesticides (Crépet, 2019). It cannot be considered as an output adopted by the Authority.…”
Section: Co-exposure To Multiple Pesticides or Exposure To Single Pesmentioning
confidence: 99%
“…Consequently, it is relevant to distinguish between exposures of persons that are exposed to multiple pesticides as listed in Table 14: and the persons that are exposed to one pesticide with a high residue concentration as shown in Table 15: . In the EU-funded project EuroMix (Grant Agreement Number 633172) 10 useful tools have been surveyed, developed and/or implemented in the MCRA software, such as the Maximum Cumulative Ratio (MCR) method and the SNMU method, to diagnose mixtures of concern and the persons exposed to multiple pesticides (Crépet, 2019 The present document has been produced and adopted by the bodies identified above as authors. In accordance with Article 36 of Regulation (EC) No 178/2002, this task has been carried out exclusively by the authors in the context of a grant agreement between the European Food Safety Authority and the authors.…”
Section: Co-exposure To Multiple Pesticides or Exposure To Single Pesmentioning
confidence: 99%
“…They suggest that these pesticides would need a high control as well as a refinement of the risk assessment to ensure their safety for the population. IMZ contributes one of the most to the European pesticide mixture exposure from national surveys in nine European countries (Crépet et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to EFSA, it is likely that even within large AGs the cumulative exposure is mainly driven by a few substances. Indeed, CRA performed for AGs based on phenomenological effect showed that cumulative exposure could be driven by only a few substances (EFSA, 2020a;Crépet et al, 2019). Therefore, EFSA proposed a prioritisation system based as described in section 1.1 and displayed in Figure 1: .…”
Section: Additional Informationmentioning
confidence: 99%
“…Annex A presents an overview hazard metrics of specific effects (van Klaveren et al, 2019(van Klaveren et al, , 2019b and critical effects (OpenFoodTox database complemented with EU pesticide database)…”
Section: Efsa Supporting Publication 2021:en-6559mentioning
confidence: 99%